1983
DOI: 10.1111/j.1471-0528.1983.tb08924.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal treatments of sexual unresponsiveness in postmenopausal women: a comparative study

Abstract: Forty postmenopausal women, referred for hormone replacement therapy and all of whom reported a significant concern about a decline in their sexual interest, were randomly allocated to one of two hormone implant treatment groups: either oestradiol (50 mg) alone, or oestradiol (50 mg) and testosterone (100 mg). Comparison between the two groups as a whole revealed no significant differences on any measure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 9 publications
0
47
0
1
Order By: Relevance
“…The first documented practical application of the original (1976) Greene Climacteric Scale dates back to 1983 [15]. A trial was performed on 40 women with varying degrees of menopausal symptoms recruited from a hormone replacement clinic.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The first documented practical application of the original (1976) Greene Climacteric Scale dates back to 1983 [15]. A trial was performed on 40 women with varying degrees of menopausal symptoms recruited from a hormone replacement clinic.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…29,32,35,37 Additionally, several of the trials demonstrated that the addition of androgens improved sense of well being and other 'psychological factors'. 30,38,42,43,46 In the one trial of premenopausal women, testosterone therapy was also found to be effective in improving sexual desire, arousal and satisfaction. 33 …”
Section: Changes To Androgen Status With Age Menopause and Medicationsmentioning
confidence: 99%
“…Subsequently, as shown in Table 2, a multitude of trials have examined the effects of testosterone on sexual function in pre-and post-menopausal women [23][24][25][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Together, these trials indicate that testosterone treatment which results in high (premenopausal) physiologic or slightly supraphysiologic testosterone levels increases arousability, desire, fantasy, frequency of sexual activity, frequency of orgasm, sexual satisfaction, and pleasure, and decreases personal distress.…”
Section: Results Of Testosterone Treatment Trials On Sexual Function mentioning
confidence: 99%